Prognostic factors of revitrectomy for complications in eyes with proliferative diabetic retinopathy: a retrospective multicentre study. Issue 4 (1st November 2019) - Takayama, Kei; Someya, Hideaki; Yokoyama, Hiroshi; Kimura, Takeshi; Takamura, Yoshihiro; Morioka, Masakazu; Sameshima, Seiji; Ueda, Tetsuo; Ogata, Nahoko; Kitano, Shigehiko; Tashiro, Maki; Sugimoto, Masahiko; et al.
Abstract: Purpose: To identify prognostic factors for revitrectomy in patients who underwent vitrectomy for complications with proliferative diabetic retinopathy (PDR) in multicentre study. Methods: Consecutive 452 eyes of 452 patients with PDR undergoing 25‐gauge microincision vitrectomy system (MIVS) in seven centres were retrospectivity reviewed. Preoperative ocular factors (baseline visual acuity [VA], vitreous haemorrhage [VH], tractional retinal detachment [TRD] and retinal photocoagulation), general factors (sex, age, diabetes duration, HbA1c level, hypertension, anti‐coagulant medication and estimated glomerular filtration rate), surgical procedures (preoperative anti‐vascular endothelial growth factor injection, internal limiting membrane peeling, combined cataract surgery, retinal break, and tamponade), postoperative complications for revitrectomy and postoperative VA at 6 months were evaluated. Results: In the follow‐up period of 6 months, revitrectomy was performed in 56 eyes (26.3%), and postoperative complications for revitrectomy were VH in 31 eyes (15%), TRD in 13 eyes (6.2%) and membrane proliferation in 12 eyes (5.2%). The mean LogMAR improvement from baseline to 6 months in revitrectomy group (0.39) was significantly worse than in single vitrectomy group (0.74). Diabetic duration, low baseline VA, less simple VH, TRD and air tamponade were statistical risk factors of revitrectomy, and logistic regression analysis identified low baseline VA and air tamponade also as prognostic factors of revitrectomy. Conclusion: Our results indicated that prognosis of VA was worse in PDR patients with revitrectomy and low baseline VA and air as the tamponade material were the potential prognostic factors of revitrectomy.